2021
DOI: 10.1007/s12036-020-09687-y
|View full text |Cite
|
Sign up to set email alerts
|

UVIT study of UV bright stars in the globular cluster NGC 4147

Abstract: We present far ultraviolet (FUV) observations of globular cluster NGC 4147 using three FUV filters, BaF 2 (F154W), sapphire (F169M), and silica (F172M) of Ultra-Violet Imaging Telescope (UVIT) onboard the AstroSat satellite. We confirmed the cluster membership of the UVIT observed sources using proper motions from Gaia data release 2 (GAIA DR2). We identified 37 blue horizontal branch stars (BHBs), one blue straggler star (BSS) and 15 variable stars using UV-optical color magnitude diagrams (CMDs). We find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Optical identification of AstroSat discovered sources was one of the prime goals of the 3.6-m DOT and the 4K×4K CCD Imager (Sagar 2018, Pandey et al2018. Recently, Kumar et al (2021) identified several AstroSat-UVIT sources in the field of NGC 4147. These objects are located in different stages of stellar evolution in the UV-optical CMDs showing properties of blue horizontal branch stars, blue straggler star and variable stars.…”
Section: The Colour-magnitude Diagram Of Ngc 4147mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical identification of AstroSat discovered sources was one of the prime goals of the 3.6-m DOT and the 4K×4K CCD Imager (Sagar 2018, Pandey et al2018. Recently, Kumar et al (2021) identified several AstroSat-UVIT sources in the field of NGC 4147. These objects are located in different stages of stellar evolution in the UV-optical CMDs showing properties of blue horizontal branch stars, blue straggler star and variable stars.…”
Section: The Colour-magnitude Diagram Of Ngc 4147mentioning
confidence: 99%
“…While Lata et al (2019) have discovered several different types of variables within core region of the NGC 4147 using optical observations taken with the 4K×4K CCD imager 2 by Lata et al (2019). It is numbered as HB24 in Table 4 of Kumar R. et al (2021).…”
Section: The Colour-magnitude Diagram Of Ngc 4147mentioning
confidence: 99%
“…However, depending upon the environment during merger or collision, the mass and age of BSs are slightly different from single star evolution (Sills et al 2009;Sun et al 2021). Due to their extremely large effective temperature, a UV imaging study is a powerful tool to identify and trace the properties of BSs in GCs (Ferraro 2000;Raso et al 2017;Ferraro et al 2018;Sindhu et al 2019;Sahu et al 2019a;Subramaniam et al 2020;Kumar et al 2021a).…”
mentioning
confidence: 99%
“…The physical parameters such as (T eff ), radius, luminosity, mass, etc., have been derived for the UV bright sources of various evolutionary stages (EHBs, BHBs, BSs, etc.) using UVIT and other available optical photometric observations (Sahu et al 2019a;Singh et al 2020;Kumar et al 2020Kumar et al , 2021aPrabhu et al 2021;Rani et al 2021). The stellar evolutionary models such as BaSTI (old) and BaSTI-IAC (updated) (Pietrinferni et al 2004;Hidalgo et al 2018;Pietrinferni et al 2021), FSPS models (Conroy et al 2009), Padova isochrone sets (Marigo & Girardi 2007), Y 2 stellar evolutionary tracks (Lee et al 2015), etc., have well incorporated in deriving these parameters.…”
mentioning
confidence: 99%